The Effect of Climate on Poultry Productivity in Ilorin Kwara State, Nigeria - Elijah, Obayelu Abiodun; Adedapo, Adeniyi (International Journal of Poultry Science, 2006)
An empirical analysis of the relationship between climatic elements, poultry feed intake, egg production and disease outbreaks in Ilorin Kwara State Nigeria was carried out using climatological data and data from poultry farmers over a period of five years (2000-2004). Data on temperature, rainfall, wind speed and relative humidity for every month in the selected years were obtained from the department of Ilorin International Airport, and analyzed. While data on poultry egg production, poultry feed intake as well as disease outbreak were collected through a stratified random sampling of 120 poultry farmers in llorin metropolis. The results of the analysis using both descriptive and inferential statistics such as mean, coefficient of variation, multiple regression analysis show that climatic variables (temperature, rainfall, wind speed and relative humidity) in Ilorin contribute about 81%, 96% and 43% to the variance in poultry egg production, feed intake and outbreak of diseases of poultry production respectively. While temperature has an inverse relationship with poultry feed intake, high relative humidity in the study area usually encourage outbreak of poultry diseases which invariably reduce egg production. In order to improve poultry productivity in Ilorin, the poultry farmers need to establish appropriate housing and sanitation practices to minimize the effect of heat and the occurrence and spread of diseases. Poultry birds must properly be confined so as to protect them from physical hazards, rain and extremes of heat and cold in order to enhance productivity. Farmers should select poultry breeds that are adaptable to the kind of climate operating in the study area. There is also the need to feed the birds with sufficient ration so as to meet their nutritional requirement.